Background paper for the establishment of governmentcontributions to the PanAfrican Control of Epizootics (PACE) programme - African Union Inter-African Bureau for Animal Resources; AU-IBAR (My University, 2021)
Background paper for the establishment of governmentcontributions to the PanAfrican Control of Epizootics (PACE) programme
Keywords: Pan-African Control of Epizootics (PACE)